Improving appraisal of sustainability of energy options – A view from Slovenia. (March 2016) - Kontić, Branko; Bohanec, Marko; Kontić, Davor; Trdin, Nejc; Matko, Maruša
Abstract: The new Slovenian approach to systematic, transparent, and reproducible appraisal of sustainability as related to electricity production is presented. The common sustainability components, i.e. economy, environment, and society, are integrated into evaluation of the feasibility, rationality, and uncertainty of the energy mix alternatives. A three stage model has been applied for this sustainability appraisal. The first level deals with alternative technologies for electricity production, the second with alternative mixtures of technologies for meeting electricity needs by 2050, and the third takes into account the expected timing of shutting-down existing old power plants and constructing the new ones. Technology alternatives cover both conventional and renewable energy sources: coal fired, gas fired, biomass fired, oil fired, nuclear, hydro, wind, and photovoltaic. The results show that only mixtures of nuclear, hydro, and gas fired technologies are reliable and rational in the context of meeting expected energy needs. The expected share of energy produced by wind and photovoltaic technology is between 8% and 15%, which makes them less sustainable than other technologies. Eventually, they do not meet sustainability goals from the economic and social points of view.